Zeitschriften als Raum der Zirkulation. Das Osteuropa-Programm im Merkur. Deutsche Zeitschrift für europäisches Denken - Zajas, Paweł (Springer, 2023)
First published in 1947 in what was then the French occupation zone, the German periodical Merkur. Deutsche Zeitschrift für europäisches Denken has played a crucial role in shaping the intellectual landscape not only of Germany, but of Europe as a whole. Since its foundation amidst rising tensions between East and West, the journal has regularly published translations from nearly all European, American, and Asian literatures, adding ample commentary and paratexts. The present paper is devoted to the dynamics of translation as they become manifest in the East European literatures published by Merkur. The analysis focuses on the following factors: 1) the research potential of the editorial archive and the influence of social factors on the circulation of literary texts; 2) the political-cultural potential of the journal; 3) Merkur’s place in the transnational field; 4) the economic and programmatic role of cooperating periodicals; and 5) the functions of mediators and translators within the framework of politicized importation of East European literature.
Keywords: Merkur; journal studies; East-European literature; literary transfer